CORRUPTION CRIME IN THE CRIMINAL EXECUTIVE SYSTEM OF THE RUSSIAN FEDERATION AND ITS PREVENTION - GIRKO, SERGEY; Kharchenko, S.V.; GIRKO, SERGEY; Kharchenko, S.V.; Latyshev, S.U. (International Journal of Psychosocial Rehabilitation, 2020)
the article analyzes determining corruption crime factors in the penal system of the Russian Federation through the analysis prism of the UN and Russian anti-corruption legislation, provides statistical information on corruption manifestations in the Russian Federation, presents the shortcomings of the legal regulation of factors aimed at combating corruption behavior in the penitentiary system